2020
DOI: 10.1016/j.apsusc.2020.146790
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural properties of Mo-S-N sputtered coatings

Abstract: Transition-metal-dichalcogenide coatings provide low friction because of characteristic low shear strength along the basal plane of the lamellar structure; however, the material can easily degrade through exfoliation and poor adhesion to the metallic substrates. In this work, an innovative approach was employed to improve the coating's adhesion. A secondary plasma source was used during deposition to generate an additional charged particle flux which was directed to the growing film independently of the magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 57 publications
(66 reference statements)
2
17
0
Order By: Relevance
“…With the increase in N content, the increasing values of the wear rate and COF were attributed to the reduced S/Mo ratio (∼0.7) which hindered the formation of the well-ordered tribo-film at the contact area leading to the failure of coating. Similar works were also reported by Nossa et al 41 In our previous work, 29 Mo−S−N coatings were deposited using a novel hybrid deposition approach to improve the composition, compactness, structure, and adhesion. It was observed that the use of the secondary plasma source allowed the N ion bombardment of the growing film.…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…With the increase in N content, the increasing values of the wear rate and COF were attributed to the reduced S/Mo ratio (∼0.7) which hindered the formation of the well-ordered tribo-film at the contact area leading to the failure of coating. Similar works were also reported by Nossa et al 41 In our previous work, 29 Mo−S−N coatings were deposited using a novel hybrid deposition approach to improve the composition, compactness, structure, and adhesion. It was observed that the use of the secondary plasma source allowed the N ion bombardment of the growing film.…”
Section: Introductionsupporting
confidence: 79%
“…The pure sputtered MoS 2 coating showed the lowest hardness values of 0.5 GPa because of its low packing density 47 and columnar morphology, in agreement with the previous study. 29 The hardness of the films increased to 1.5 GPa (Mo−S−N10, 18 atom % N) as soon as nitrogen was introduced in the chamber. The hardness continued to increase with further additions of nitrogen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The interface of MoS 2 with the steel substrate can often be a point of failure by delamination due to the abrupt change in material properties causing stress concentrations at the interface. [ 44 ] To address this, adhesion layers are often employed as seen for the thick WC layer of MoS 2 +WC and very thin layers for MoS 2 +Ta and MoS 2 +Ti. Figure 1E–H shows the cross‐sectional high‐resolution transmission electron microscopy (HRTEM) images of the four coatings inset with the selected area electron diffraction (SAED) pattern.…”
Section: Mos2 Co‐deposition With Tantalummentioning
confidence: 99%